The Effect of Board Composition on Performance with Emphasis on Efficiency of Firm’s Total Resources Value Added - Mohamad Namazi; Fahimeh Ebrahimi (مطالعات تجربی حسابداری مالی, 2012)
This study aims to investigate to the effect of board composition on performance of companies Tehran Stock Exchange listed with emphasis on efficiency of value added by a firm’s total resources and efficiency of value added by a firm’s physical capital and intellectual capital resources separately. For this purpose, a sample consisting of 64 companies between 2001 and 2010 was selected. The results of testing hypotheses by applying the ordinary least square regression model statistically show that there is a weak positive and meaningful relationship between the variable of the presence of one of the non-executive members in the chairman position and the efficiency of value added by a firm’s total resources and efficiency of value added by a firm’s physical capital and intellectual capital resources. However, no meaningful relationship was found between variables of the percentage of non-executive directors on the board and presence of at least three non-executive members in the board composition and the efficiency of value added by a firm’s total resources and efficiency of value added by a firm’s physical capital and intellectual capital resources